(untitled) (Modern education and development, 2025)
This paper examines the impact of investment on economic growth and development, emphasizing the roles of foreign direct investment (FDI), domestic investment, and public investment. A review of empirical literature reveals the conditional nature of FDI’s effectiveness, influenced by factors such as political stability, regulatory frameworks, and infrastructure. Using econometric models, the study finds a strong positive correlation between investment and GDP growth, particularly in developing economies. Uzbekistan serves as a case study, highlighting its investment-driven transformation since 2017. Key sectors attracting FDI include manufacturing, energy, and digital technology, with China, Russia, and the U.S. playing major roles. Despite economic gains, challenges such as debt management, regulatory inefficiencies, and reliance on limited trade partners persist. The paper underscores the need for policy-driven investment strategies to sustain long-term economic growth.